Comparison between Retroperitoneal Laparoscopic Nephrectomy and Traditional Open Nephrectomy to Treat Polycystic Kidney Disease before Kidney Transplantation - Lyu, Jingcheng; Du , Chun-Kai; Zhu, Yichen (Urology Journal, 2024)
Purpose: To compare the efficiency and safety between retroperitoneal laparoscopic nephrectomy and traditional open nephrectomy to treat autosomal-dominant polycystic kidney disease before kidney transplantation. Materials and Methods: A total of 57 patients diagnosed with huge autosomal-dominant polycystic kidney disease between 2000 and 2020 at our center were included in this study. Patients were divided into a retroperitoneal laparoscopic (RL; n=23) group and traditional open (TO; n = 34) group. We retrospectively analyzed and compared preoperative and perioperative variables between the two groups. Results: Patients in the RL group showed a longer operation time (201.09±83.76min) compared to patients in the TO group (113.38 ± 51.84min, p < 0.001). The RL group also showed significantly less intraoperative blood loss (p = 0.025) and less intraoperative blood transfusion volume (p = 0.016) compared to the TO group. Meanwhile, time of gastrointestinal function recovery, bed leave, catheter indwelling and postoperative hospitalization in the RL group were 2.13 ± 0.63, 1.30 ± 1.0, 5.22 ± 2.09, 7.35±2.48 days, respectively, which were significantly shorter than the TO group (p < 0.05). Pain degree of patients during the first 48 hours after operation was similar between the RL and TO groups, but the opioid use percentage in the RL group was 8.70% (2/23) and was lower than the 26.47% (9/34) in the TO group (p = 0.022). Meanwhile, 5 and 23 patients exhibited postoperative complications in the RL and TO groups, respectively (p < 0.001). Conclusion: Both retroperitoneal laparoscopic nephrectomy and traditional open surgery are feasible to treat huge polycystic nephrectomy. However, patients who undergo retroperitoneal laparoscopic nephrectomy experience higher levels of safety and recover more rapidly.